Teacher-Parent collaboration in the development of Individualised Education Programme (IEP) for special education - Nora Mislan (Universiti Kebangsaan Malaysia, 2009)
The purpose of this study was to examine the roles of teacher-parent collaboration in the implementation of the Individualised Education Programme (IEP) in special education in Malaysia. IEP must be designed and written for students with disabilities to cater for their unique individual needs. Teachers and parents are expected to work in partnership to determine the goals and programmes that are appropriate for the students. Thus, the IEP process should be taken seriously as it is one of the crucial factors in the bid to improve the services provided for students with disabilities. Writing and executing an effective IEP is critical since IEP provides the basis for quality education for these students. Taking this into consideration, feedback from parents regarding their expectations is vital in developing effective special education programmes.